Analisis Metode Perhitungan Zakat pada Bank Syariah Indonesia - Asrida Asrida; Atika Amor (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to analyze the zakat calculation method carried out by Bank Syariah Indonesia. The zakat calculation method used by Bank Syariah Indonesia will be compared with the method issued by AAOIFI and BAZNAS. This type of research is qualitative with a descriptive approach. The document used in this research is the financial report of Bank Syariah Indonesia which was published in 2023. The data analysis technique in this research is content analysis technique. The research results show that Bank Syariah Indonesia uses a profit account before zakat and tax multiplied by 2.5% as the basis for calculating zakat. Bank Syariah Indonesia zakat potential if calculated using the AAOIFI and BAZNAS methods reaches 3 to 4 times the amount of zakat currently issued. Bank Syariah Indonesia zakat has the potential to be greater using the Net Invested Fund method, namely Rp 859,696 billion.